Formal verification of side channel countermeasures using self-composition - Almeida, José Bacelar (2011)
Formal verification of cryptographic software implementations poses significant challenges for off-the-shelf tools. This is due to the domain-specific characteristics of the code, involving aggressive optimisations and non-functional security requirements, namely the critical aspect of countermeasures against side-channel attacks. In this paper we extend previous results supporting the practicality of self-composition proofs of non-interference and generalisations thereof. We tackle the formal verification of high-level security policies adopted in the implementation of the recently proposed NaCl cryptographic library. We formalize these policies and propose a formal verification approach based on self-composition, extending the range of security policies that could previously be handled using this technique. We demonstrate our results by addressing compliance with the NaCl security policies in real-world cryptographic code, highlighting the potential for automation of our techniques.